The Attractiveness of Green Areas in the Wola District for the Purposes of Recreation of the Teachers and Students - Strumińska-Doktór, Anna; Doktór, Dobromiła (Studia Ecologiae et Bioethicae, 2016)
Striving for a healthy lifestyle depends on habits. These habits, thanks to the family and the school will be inherited by successive generations. The article presents the contribution of teachers in shaping the attitude promoting the outdoor activities. In the Wola district, the green areas are used during the classes in the school throughout the school year. Unfortunately, the frequency of use of the nearby parks is very moderate when it comes to activities conducted during different classes, and to practice the active forms of recreation, the teachers and children several times a week use the green areas of Wola district. Large green areas are important lungs of the district and the city. These areas can also be used to conduct school tours to explore the surrounding nature. By the way, it should be noted that the green areas of Wola district are under a careful concern. Apart from the environmental function (biological, climatic and hydrological) they play important non-environmental functions, among others, educational, recreational, leisure, and aesthetic. The Wola district, given the significant role played by the green areas, takes into account the investment tasks related to green areas in long-term planning, on an ongoing basis the parks are being modernized, new recreation areas and playgrounds are created, which emphasizes the recreational role of these areas but also the educational value because of their huge historical importance.